Plasmodium falciparum expresses fewer var genes at lower levels during asymptomatic dry season infections than clinical malaria cases. - Sukai Ceesay; Martin Kampmann; Lasse Votborg-Novél; Helle Smedegaard Hansson; Rasmus Weisel Jensen; Manuela Carrasquilla; Hamidou Cisse; Louise Turner; Usama Dabbas; Christina Ntalla; Silke Bandermann; Safiatou Doumbo; et al. (PLoS Pathogens)
In seasonal transmission areas, clinical malaria occurs during the wet season when mosquitoes are present, while in the dry season, malaria transmission is interrupted and clinical cases are rare. In Mali, Plasmodium falciparum can persist in low parasitaemic asymptomatic individuals through the six-month dry season and shows circulation of more developed parasite stages compared to clinical malaria cases, indicative of reduced cytoadhesion of infected erythrocytes. How prolonged circulation of infected erythrocytes is achieved remains unknown. Here, we explored var gene expression in subclinical infections and clinical malaria cases of Malian children, collected during the dry and wet seasons. We sequenced expressed var DBLα-tags, used bioinformatic tools to predict their domain composition, binding phenotype and upstream sequence type; and determined their relationship to seasonality and clinical presentation. We found that parasites of asymptomatic infections expressed fewer var genes, with a larger proportion of var transcripts attributed to one or a few vars. In contrast, clinical cases exhibited expression of many var genes at lower proportions. We found that parasites of asymptomatic carriers expressed a mixture of CD36- and EPCR-binding PfEMP1, which changed over time. We confirmed that vars encoding CD36-binding PfEMP1 dominated in non-severe malaria cases, and found no significant difference in expressed var types between dry and wet seasons. Asymptomatic carriers were older, had higher titers of anti-P. falciparum antibodies, and broader reactivity to PfEMP1, suggesting that host immunity was the main determinant limiting var transcript variation in asymptomatic carriers. However, qRT-PCR analyses also indicated higher total var transcript levels in malaria cases compared to asymptomatic carriers, suggesting that in addition to the parasite's switching and the host's immune selection of expressed var genes, parasites able to sustain long-term infections may be poised for reduced PfEMP1 expression.